Geometric Analysis of the Road on the Pramuka Road Section in Harjamukti District, Cirebon City, West Java Province STA 0+000 – STA 2+000 - Haekal, Adi Muhammad; Kurnianto, Muhammad Fajar; Dewi, Adinda Sabina; Sudrajat, Kukuh Mahi; Isradi, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Road infrastructure design is an important component in the land transportation system that serves to improve mobility, safety, and comfort for road users. This study discusses the infrastructure planning of Jalan Pramuka, located in Harjamukti District, Cirebon City, with a route length of ±2.3 km. The main objective is to produce design recommendations that not only improve safety and efficiency but are also environmentally and economically sustainab. The research methodology includes the collection of primary and secondary data, including topography, road geometry, traffic, subgrade conditions, and hydrology data. The analysis covers horizontal and vertical alignment planning, road pavement structure analysis, drainage system design, and construction cost analysis. All collected data were subsequently used as the basis for geometric analysis, pavement planning, drainage design, and construction cost analysis. Road geometric planning was carried out with a design speed of 70 km/h and considered safety aspects through the use of spiral-circle-spiral (SCS) curves. Pavement analysis was based on the average daily traffic (ADT) in the design year 2025 and a subgrade CBR value of 5.5%, with a pavement design life of 15 years. The drainage system was designed using trapezoidal channels capable of accommodating rainfall discharge in accordance with the rainfall in the study area. The planning results show that the proposed road design meets applicable technical standards and is expected to support smooth traffic flow and sustainable regional development.